Identification of promising sources of barley (Hordeum vulgare L) for malt beta-glucanase activity and wort beta-glucan content - Kumar, Dinesh; Verma, Ramesh Pal Singh; Kumar, Lokendra; Kumar, Vishnu; Singh, Gyanendra Pratap (Journal of Cereal Research, 2022)
Five genotypes along with four checks were grown at six locations during the rabi season of 2020-21 and grains were malted and mashed. The genotypes ICARDA-11, ICARDA-9 and DWRB 197 registered the higher malt beta glucanase activity as compared to the checks, with average value more than 370U/kg.Â Two genotypes, ICARDA-11 and ICARDA-9 were identified with very low wort beta glucans content well below than 200 ppm, the current required levels. These genotypes can be potential sources of these two traits in malt improvement programme of the country.